(untitled) (New York, 1995)
In this second edition, standards and criteria are affecting the design of apartment buildings and the organization of the neighborhood.
Keywords: Homesites,Dwellings,Thiết kế nhà; Planning,Handbooks, manuals, etc.,Designs and plans,Handbooks, manuals, etc